2008
DOI: 10.1097/mao.0b013e31818a086e
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo and Clinical Test of Sensory Interaction and Balance in Systemic Sclerosis

Abstract: The present study shows an increased frequency of BPPV and a vestibular pattern in CTSIB in SSc patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Amor-Dorado et al (12,17) and Maciaszczyk et al (13) had differences in the study population with regard to the form of disease (limited or diffuse); however, only in the analysis by Amor-Dorado et al (12) results were presented by considering the type of disease. Prevalence of changes in the vestibular system was higher for patients with diffuse SS (Charts 1 and 2).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Amor-Dorado et al (12,17) and Maciaszczyk et al (13) had differences in the study population with regard to the form of disease (limited or diffuse); however, only in the analysis by Amor-Dorado et al (12) results were presented by considering the type of disease. Prevalence of changes in the vestibular system was higher for patients with diffuse SS (Charts 1 and 2).…”
Section: Resultsmentioning
confidence: 81%
“…The largest sample was observed in the study by AmorDorado et al (12) , which included 42 individuals with SS, and the smallest sample was observed in the study by Maciaszczyk et al (13) , including 20 people diagnosed with SS. The reduced number of the samples is probably because of the fact that SS is a rare and progressive disease, with several incapacitating manifestations leading to death.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Rheumatoid arthritis, an immune-mediated systemic disorder, can also affect the inner ear and can cause high-frequency hearing loss [25] . A high percentage of BPPV in patients with giant cell arteritis and systemic sclerosis also demonstrates that immune-mediated inflammatory ischemia may play a role in BPPV [3,26] .…”
Section: Discussionmentioning
confidence: 99%